Discriminative Validity of Vestibular Ocular Motor Screening in Identifying Concussion Among Collegiate Athletes: A National Collegiate Athletic Association–Department of Defense Concussion Assessment, Research, and Education Consortium Study. Issue 8 (July 2021) - Kontos, Anthony P.; Eagle, Shawn R.; Marchetti, Gregory; Sinnott, Aaron; Mucha, Anne; Port, Nicholas; Ferris, Lyndsey M.; Elbin, R.J.; Clugston, James R.; Ortega, Justus; Broglio, Steven P.; McAllister, Thomas; et al.
Background: Vestibular and ocular motor screening tools, such as the Vestibular/Ocular Motor Screening (VOMS), are recognized as important components of a multifaceted evaluation of sport-related concussion. Previous research has supported the predictive utility of the VOMS in identifying concussion, but researchers have yet to examine the predictive utility of the VOMS among collegiate athletes in the first few days after injury. Purpose: To determine the discriminative validity of individual VOMS item scores and an overall VOMS score for identifying collegiate athletes with an acute sport-related concussion (≤72 hours) from healthy controls matched by age, sex, and concussion history. Study Design: Case-control study; Level of evidence, 3. Methods: Participants (N = 570) aged 17 to 25 years were included from 8 institutions of the National Collegiate Athletic Association–Department of Defense CARE Consortium (Concussion Assessment, Research, and Education): 285 athletes who were concussed (per current consensus guidelines) and 285 healthy controls matched by age, sex, and concussion history. Participants completed the VOMS within 3 days of injury (concussion) or during preseason (ie, baseline; control). Symptoms are totaled for each VOMS item for an item score (maximum, 40) and totaled across items for an overall score (maximum, 280), and distance (centimeters) for near point of convergence (NPC) is averaged across 3 trials. Receiver operating characteristic analysis of the area under the curve (AUC) was performed on cutoff scores using Youden index ( J ) for each VOMS item, overall VOMS score, and NPC distance average. A logistic regression was conducted to identify which VOMS scores identified concussed status. Results: A symptom score ≥1 on each VOMS item and horizontal vestibular/ocular reflex ≥2 significantly discriminated concussion from control (AUC, 0.89-0.90). NPC distance did not significantly identify concussion from control (AUC, 0.51). The VOMS overall score had the highest accuracy (AUC, 0.91) for identifying sport-related concussion from control. Among the individual items, vertical saccades ≥1 and horizontal vestibular/ocular reflex ≥2 best discriminated concussion from control. Conclusion: The findings indicate that individual VOMS items and overall VOMS scores are useful in identifying concussion in collegiate athletes within 3 days of injury. Clinicians can use the cutoffs from this study to help identify concussion in collegiate athletes.